2011
DOI: 10.1007/s10535-011-0032-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic transformation of barley: limiting factors

Abstract: This review summarizes main difficulties involved in barley (Hordeum vulgare L.) transformation. The most commonly used procedures for genetic transformation in barley are Agrobacterium tumefaciens and particle bombardment mediated methods. While different barley cultivars are used for genetic engineering with varying sensitivity, recent improvements in regeneration and transformation techniques are described and summarized. Furthermore, some of the transformation complicating factors, in particular somaclonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 102 publications
1
3
0
1
Order By: Relevance
“…S2e). Such abnormalities have already been described in several publications for transformant plants (reviewed by Vyroubalová et al 2011), but we found that the PITP and PI4K transformants showed this abnormality in a relatively higher rate. In the PI4K L6 line, 6.5% of the plants showed a pale leaf phenotype, while in the PI4K L4 line 6%, and in the PITP L11 line 5% of the plants showed albinism.…”
Section: Developmental Disorders Of the Transgenic Linessupporting
confidence: 80%
“…S2e). Such abnormalities have already been described in several publications for transformant plants (reviewed by Vyroubalová et al 2011), but we found that the PITP and PI4K transformants showed this abnormality in a relatively higher rate. In the PI4K L6 line, 6.5% of the plants showed a pale leaf phenotype, while in the PI4K L4 line 6%, and in the PITP L11 line 5% of the plants showed albinism.…”
Section: Developmental Disorders Of the Transgenic Linessupporting
confidence: 80%
“…Genetic engineering is a useful approach for creating crop plants with desired qualities. Since cereal species have immense agricultural importance, there have been many recent advances in transformation techniques for monocot plants [1] allowing rapid development of novel transgenic varieties. Barley ( Hordeum vulgare L.) is a widely grown cereal with valuable traits, including high malting quality and nutritional value, which are exploited in brewing, distilling and the production of diverse human and animal foods.…”
Section: Introductionmentioning
confidence: 99%
“…Plant transformation is essential for crop improvement and a wide range of basic research such as understanding gene functions and precision gene editing (Lawrenson et al 2015 ; Hinchliffe and Harwood 2019 ). Since the first transgenic barley was generated with microprojectile bombardment (Ritala et al 1994 ; Wan and Lemaux 1994 ), several barley transformation systems have been developed, but the Agrobacterium-mediated transformation with immature embryo explants by somatic embryogenesis is the most widely used procedures for genetic transformation in barley as it can yield higher transformation efficiency (Tingay et al 1997 ; Vyroubalová et al 2011 ). However, this transformation system only works for limited barley genotypes and failed to generate transgenic plants for many elite barley cultivars.…”
Section: Introductionmentioning
confidence: 99%